HYBRID CATALYSTS FOR THE HYDROCARBON SYNTHESIS PROCESS FROM CO AND H2 (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The strategy for creating a low-energy and consequently efficient GTL technology is to improve the hydrocarbon synthesis step by adjusting the selectivity of the process for the desired products by choosing catalysts and conditions that allow obtaining fuel fractions. one stage.